2016
DOI: 10.5194/bg-13-4959-2016
|View full text |Cite
|
Sign up to set email alerts
|

Spring blooms in the Baltic Sea have weakened but lengthened from 2000 to 2014

Abstract: Abstract. Phytoplankton spring bloom phenology was derived from a 15-year time series (2000–2014) of ship-of-opportunity chlorophyll a fluorescence observations collected in the Baltic Sea through the Alg@line network. Decadal trends were analysed against inter-annual variability in bloom timing and intensity, and environmental drivers (nutrient concentration, temperature, radiation level, wind speed).Spring blooms developed from the south to the north, with the first blooms peaking mid-March in the Bay of Mec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 69 publications
7
51
0
Order By: Relevance
“…Consequently, the spring bloom has an intense but short-lived impact on the optical properties of the surface layer [54,55]. In contrast, thermal stratification in summer causes the summer particle population to linger in surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the spring bloom has an intense but short-lived impact on the optical properties of the surface layer [54,55]. In contrast, thermal stratification in summer causes the summer particle population to linger in surface waters.…”
Section: Discussionmentioning
confidence: 99%
“…At present, freshwater induced stratification is important for the initial start of the spring bloom, but thermal stratification may become more important in the future (Hordoir and Meier, 2012). Warming of the Baltic Sea has already caused temporal shifts in the phytoplankton distribution during the highly productive spring, with earlier and more prolonged spring bloom (Groetsch et al, 2016;Kahru et al, 2016). In addition, longterm monitoring data suggest that the phytoplankton community is changing during spring in some areas of the Baltic Sea from diatom to dinoflagellates dominance , as a consequence of the ongoing climate change (Klais et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, in the Baltic Sea, investigators found that bloom duration has increased in recent years and associated this change in bloom dynamics with increasing water temperature and declining wind stress, which they attributed to global climate change (Groetsch, Simis, Eleveld, & Peters, 2016). As climate systems shift in response to anthropogenic forcing, there is a need to understand their impact on bloom dynamics both retrospectively and in a forecasting context.…”
mentioning
confidence: 99%
“…As climate systems shift in response to anthropogenic forcing, there is a need to understand their impact on bloom dynamics both retrospectively and in a forecasting context. As an example, in the Baltic Sea, investigators found that bloom duration has increased in recent years and associated this change in bloom dynamics with increasing water temperature and declining wind stress, which they attributed to global climate change (Groetsch, Simis, Eleveld, & Peters, 2016). Change in climate conditions may act to modify blooms through the direct effects of nutrient supply and grazing; additionally, changing distributions of parasites and viruses associated with climate change will be likely to play a larger role in the dynamics of blooms and the nature of fixed carbon available to primary grazers (Frenken et al, 2016).…”
mentioning
confidence: 99%